2013
DOI: 10.36076/ppj.2013/16/e731
|View full text |Cite
|
Sign up to set email alerts
|

Fluoroscopy Procedure and Equipment Changes to Reduce Staff Radiation Exposure in the Interventional Spine Suite

Abstract: Background: Fluoroscopic guided percutaneous interventional spine procedures are increasingly performed in recent years as they have been shown to be target specific and enhance patient safety. However, ionizing radiation has been associated with stochastic effects such as cancer and genetic defects as well as deterministic effects such as cataracts, erythema, epilation, and even death. These are dose related, and hence, measures should be taken to minimize radiation exposure to patients and health care person… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Next, to maximize distance, the participants were instructed to take at least one step back from the C-arm before any images being taken. Last, shielding was strictly enforced for all participants in the form of lead vests, thyroid shields, and lead glasses 6,7 . Residents were reminded that increased radiation exposure among physicians using fluoroscopy can cause negative health effects, including erythema, cataracts, cancer, or even death.…”
Section: Methodsmentioning
confidence: 99%
“…Next, to maximize distance, the participants were instructed to take at least one step back from the C-arm before any images being taken. Last, shielding was strictly enforced for all participants in the form of lead vests, thyroid shields, and lead glasses 6,7 . Residents were reminded that increased radiation exposure among physicians using fluoroscopy can cause negative health effects, including erythema, cataracts, cancer, or even death.…”
Section: Methodsmentioning
confidence: 99%
“…Of note, Li et al reported alarmingly high effective doses in a substantial number of patients who had one or more FGP [6]. A combination of training, protective equipment, and technological innovations have the potential to reduce radiation exposure in the interventional radiology suite [7][8][9][10][11]. The precautionary guidelines of the International Atomic Energy Agency (IAEA) should be used when working with radiation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, when fluoroscopy is used, both the patient and the medical staff are exposed to ionizing radiation, which could be harmful to their health (Giordano et al, 2008) (Frane & Bitterman, 2020) (Bang et al, 2020) (Plastaras et al, 2013). Reducing radiation exposure is important for keeping patients safe and protecting healthcare workers who are often exposed to imaging methods that use radiation (Ploussi & Efstathopoulos, 2016) (Le Heron et al, 2010) (Furlow, 2011).…”
mentioning
confidence: 99%